Dissimilar gene repertoires of Dickeya solani involved in the colonization of lesions and roots of Solanum tuberosum - Robic, Kévin; Munier, Euphrasie; Effantin, Géraldine; Lachat, Joy; Naquin, Delphine; Gueguen, Erwan; Faure, Denis (Frontiers in Plant Science, 2023)
Dickeya and Pectobacterium species are necrotrophic pathogens that macerate stems (blackleg disease) and tubers (soft rot disease) of Solanum tuberosum. They proliferate by exploiting plant cell remains. They also colonize roots, even if no symptoms are observed. Genes involved in the pre-symptomatic colonization of roots are poorly known. Here, transposon-sequencing (Tn-seq) analysis of D. solani living in macerated tissues revealed 126 genes important for competitive colonization of tuber lesions and 207 for stem lesions, including 96 genes common to both conditions. Among those in common are acr genes involved in the detoxification of plant defense phytoalexins and kduD, kduI, eda (=kdgA), gudD, garK, garL and garR genes in the assimilation of pectin and galactarate. In root colonization, Tn-seq highlighted 83 genes, all different from those in maceration conditions. They encode the exploitation of organic and mineral nutrients (dpp, ddp, dctA and pst), including glucuronate (kdgK and yeiQ), and synthesis of metabolites: cellulose (celY and bcs), aryl polyene (ape) and oocydin (ooc). We constructed in-frame deletion mutant of bcsA, ddpA, apeH and pstA genes. All mutants were virulent in stem infection assays, while they were impaired in competitive colonization of roots. In addition, ∆pstA mutant was impaired in its capacity to colonize progeny-tubers. Overall, this work distinguished two metabolic networks supporting either an oligotrophic lifestyle on roots or a copiotrophic lifestyle in lesions. This work highlighted novel traits and pathways important to understand how D. solani pathogen efficiently survives on roots, persists in environment and colonizes progeny-tubers.